La deforestación como fuente de recursos económicos y su afectación al medio ambiente de la parroquia El Progreso, cantón Pasaje - Maza Cueva, Marco Antonio (My University, 2021)
This research work is of a qualitative nature and a bibliographic review, where the issue of deforestation will be addressed, considered an atmospheric phenomenon that for some time has been causing controversy worldwide, due to the great consequences that are generated from the same, being considered as an environmental problem within the planetary system. In the El Progreso parish of the Pasaje canton, deforestation is gaining strength, due to the increase in the felling of trees and the disappearance of animal species and as a factor causing this phenomenon are the residents who, due to their unconsciousness and thirst for economic income, do not they measure the consequences they cause to the earth's atmosphere, flora and fauna. From the approach of Community Social Work to the phenomenon of deforestation, it is possible to intervene directly with the inhabitants of the El Progreso parish, having the social worker the capacity and expertise to address these situations and find feasible alternatives that facilitate people to adapt to other activities that generate economic resources without harming the social and environmental environment. In this way, the main objective is to determine the intervention of Community Social Work in the face of deforestation in the El Progreso parish, Pasaje canton, through informative workshops that train its inhabitants on the consequences of environmental deforestation and talks for the Orientation to other activities that generate sources of work and economic resources that do not cause alterations to the environment.
El presente trabajo de investigación es de carácter cualitativo y de revisión bibliográfica, donde se abordará el tema de la deforestación, considerado un fenómeno atmosférico que desde tiempo atrás ha venido causando controversia a nivel mundial, debido a las grandes consecuencias que se generan a partir de la misma, siendo considerado como un problema medioambiental dentro del sistema planetario. En la parroquia El Progreso del cantón Pasaje la deforestación está cobrando fuerza, debido al incremento de la tala de árboles y la desaparición de especies de animales y como factor causante de este fenómeno están los moradores que, por su inconciencia y sed de ingresos económicos no miden las consecuencias que provocan a la atmósfera terrestre, la flora y la fauna. Desde el enfoque del Trabajo Social Comunitario ante el fenómeno de la deforestación se puede intervenir de forma directa con los moradores de la parroquia El Progreso, teniendo el trabajador social la capacidad y experticia para abordar estas situaciones y encontrar alternativas factibles que faciliten a las personas adaptarse a otras actividades que generen recursos económicos sin perjudicar al entorno social y ambiental. De tal manera, se tiene como objetivo primordial determinar la intervención del Trabajo Social Comunitario ante la problemática de la deforestación en la parroquia El Progreso, cantón Pasaje, mediante talleres informativos que capaciten a sus habitantes sobre las consecuencias de la deforestación ambiental y charlas para la orientación a otras actividades que generen fuentes de trabajo y recursos económicos que no ocasionen alteraciones al medio ambiente
Keywords: DEFORESTACION; BIODIVERSIDAD; HABITANTE; TRABAJO SOCIAL